2013
DOI: 10.1167/iovs.12-11467
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Cup-to-Disc Ratio and Estimated Number of Retinal Ganglion Cells

Abstract: PURPOSE. To investigate the relationship between cup-to-disc ratio (CDR) and estimates of retinal ganglion cell (RGC) number.METHODS. This cross-sectional study included 156 healthy eyes, 53 glaucoma suspects, and 127 eyes with glaucoma. All eyes had standard automated perimetry (SAP), Cirrus SD-OCT, and stereoscopic optic disc photography within 6 months. CDR was determined from stereoscopic photographs by two or more masked graders. The number of RGCs in each eye was estimated using a published model that co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 44 publications
3
45
0
Order By: Relevance
“…However, this limitation applies to most measurements obtained in clinical practice from imaging devices and other instruments and the formulas have been validated in multiple external human cohorts. (2224,44) A further limitation is that although the temporal cpRNFL thickness was used for the structural component of the macular RGC estimate, the exact location of the axons from macular RGCs is not known and may vary between individuals. Furthermore, although the ONH and macular scans were acquired sequentially, and scans were reviewed by the imaging center, there may have been small undetected differences in patient head or eye position that could have influenced measurements.…”
Section: Discussionmentioning
confidence: 99%
“…However, this limitation applies to most measurements obtained in clinical practice from imaging devices and other instruments and the formulas have been validated in multiple external human cohorts. (2224,44) A further limitation is that although the temporal cpRNFL thickness was used for the structural component of the macular RGC estimate, the exact location of the axons from macular RGCs is not known and may vary between individuals. Furthermore, although the ONH and macular scans were acquired sequentially, and scans were reviewed by the imaging center, there may have been small undetected differences in patient head or eye position that could have influenced measurements.…”
Section: Discussionmentioning
confidence: 99%
“…Measurements of the neuroretinal rim area of ONH were done by HRT II and expressed in mm 2 (Fig. 2).…”
Section: Neuroretinal Rim Areamentioning
confidence: 99%
“…POAG is a slowly progressing bilateral chronic optic neuropathy characterized by RGC loss and morphological changes in the optic nerve head (ONH) with thinning of the neuroretinal rim and enlargement of the optic disc cup. Histologic studies have shown the nerve fi bers of greater diameter to decay more rapidly than those with a mean diameter and this loss of large axons is most common in the inferior and superior poles of the optic disc [2][3][4][5] . Studies have demonstrated that mechanical stress could cause physical alterations in the ONH, such as misalignment of the fenestrate in lamina cribrosa, which may lead to axoplasmic fl ow obstruction due to its back bowing.…”
Section: Introductionmentioning
confidence: 99%
“…In assessing the optic nerve, Tatham et al 10 postulated a nonlinear relationship between retinal ganglion cell (RGC) estimate and cup-to-disc ratio. They concluded that cup-to-disc ratio is not sensitive for evaluating progressive neural losses in glaucoma, as small changes can be associated with large losses of RGCs.…”
Section: Optic Nerve Imagingmentioning
confidence: 99%
“…They concluded that cup-to-disc ratio is not sensitive for evaluating progressive neural losses in glaucoma, as small changes can be associated with large losses of RGCs. 10 …”
Section: Optic Nerve Imagingmentioning
confidence: 99%